Product Market Competition and Economic Performance in Sweden - Roseveare, Deborah (OECD Economics Department Working Papers, 2004)
Vigorous product market competition plays a central role in bolstering productivity growth. Sweden has strengthened competition legislation and deregulated a number of sectors, including electricity, telecommunications and parts of transport, over the past 10 to 15 years. This paper examines the current state of product market competition and proposes further measures. A stronger institutional framework would facilitate identification and elimination of anti-competitive behaviour, such as hard-core cartels. Efforts to inject effective competition into a range of network industries have been broadly successful, but specific measures could increase competition in several sectors, such as retail and construction. There is also room to boost competition in Sweden's large and decentralised public sector and in its interactions with the private sector, so that competitive neutrality applies to all public sector activities ...